Espectrometria de massas de ionização e análise sensorial de cachaças de alambique e coluna. - Andréa Carrara Geöcze (2012)
The Brazilian artisan sugar-cane spirit (cachaça) is produced by batch distillation in copper stills, which act as chemical reactors, favoring the formation of volatile componentes in the final product and improving the sensory quality of the drink. In the manufacture of industrial cachaça, there is a greater volume of production and the distillation is carried out continuously in stainless steel columns. [...]